Trade union membership and paid vacation in Germany - Laszlo Goerke; Sabrina Jeworrek; Markus Pannenberg (IZA Journal of Labor Economics, 2015)
In Germany, dependent employees take almost 30 days of paid vacation annually. We enquire whether an individual's trade union membership affects the duration of vacation. Using data from the German Socio-Economic Panel (SOEP) for the period 1985 to 2010 and employing pooled OLS-estimators, we find that being a union member goes along with almost one additional day of vacation per year. Estimations exploiting the panel structure of our data suggest that a smaller part of this vacation differential can be due to the union membership status, while self-selection effects play a more important role.
Keywords: J22; J33; J51; J81; 330; German Socio-Economic Panel (SOEP); Paid vacation; Trade union membership